Publication and dating of the journals forming the Annals and Magazine of Natural History and the Journal of Natural History - Evenhuis, Neal L. (Zootaxa, 2003)
Pagination and dates of publication for almost 2,000 separate issues of the journals that formed the Annals and Magazine of Natural History and the Journal of Natural History are presented. These journals include: Magazine of Natural History (1828–1840), Magazine of Zoology and Botany (1836–1838), Annals of Natural History (1838–1840), the Annals and Magazine of Natural History (1841–1967), and the Journal of Natural History (1967–date).